Kinome Analysis of Host Response to Mycobacterial Infection: a Novel Technique in Proteomics - Hestvik, Anne Lise K. (American Society for Microbiology, 2003)
An array of mammalian phospho-specific antibodies was used to screen for a host response upon mycobacterial infection, reflected as changes in host protein phosphorylation. Changes in the phosphorylation state of 31 known signaling molecules were tracked after infection with live or heat killed Mycobacterium bovis BCG or after incubation with the mycobacterial cell wall component lipoarabinomannan (LAM). Mycobacterial infection triggers a signaling cascade leading to activation of stress-activated protein kinase and its subsequent downstream target, c-Jun. Mycobacteria were also shown to inhibit the activation of protein kinase C ɛ and to induce phosphorylation of proteins not yet known to be involved in mycobacterial infection, such as the cytoskeletal protein α-adducin, glycogen synthase kinase 3β, and a receptor subunit involved in regulation of intracellular Ca(2+) levels. The mycobacterial cell wall component LAM has been identified as a trigger for some of these modulation events.